The relationship between social perception, peer and parental influence on students enrolment into agriculture programs in Polytechnic - Hashim, Suhaizal; Khamis, Nurhani; Edmond, Nelina; Nincarean, Danakorn (Universiti Teknologi Mara Cawangan Pulau Pinang, 2025)
This study examines the decreasing enrolment in agricultural education programs at Polytechnic Sandakan, Sabah, Malaysia, and analyses the principal factors affecting students' choices to engage in these programs. The study underscores the significance of agriculture in ensuring national food security and economic stability, while acknowledging the threats posed by diminishing interest among youth, which is linked to social factors. The study employed a quantitative methodology to survey 306 students enrolled in agriculture programs. Research indicates that students perceive agriculture favourably, acknowledging its capacity for reliable work. The average score for social perception was 3.92 (M=3.92, SD=0.99). Parental influence was identified as the most significant element (M=3.59, SD=0.99), with direct encouragement and emotional support being pivotal components. Peer influence was significant (M=3.41, SD=1.09), since students frequently depend on their social networks for affirmation in academic decisions. The Pearson correlation coefficient analysis revealed strong positive correlations among the three independent variables: social perceptions, peer influence, and parental influence. The correlation between social perception and parental influence was 0.68 (p<0.001), between social perception and peer influence was 0.50 (p<0.001), and between parental influence and peer influence was 0.70 (p<0.001). This signifies that these things are interrelated and mutually reinforcing. The study emphasises the necessity for focused initiatives, including awareness campaigns and curriculum revisions, to transform the perception of agriculture into a contemporary and esteemed professional option. Legislative reforms advocating for family and community participation, experiential learning, and peer mentorship are suggested to enhance youth engagement in agriculture education.